Effects of seasonality and developed land cover on Culex mosquito abundance and microbiome diversity - Yan, Jiayue; Green, Kirk; Noel, Kylee; Kim, Chang-Hyun; Stone, Chris M. (Frontiers in Microbiology, 2024)
The vectorial capacity of mosquitoes, which influences the dynamics of vector-borne disease transmission, is intricately linked to mosquito abundance and the composition and diversity of their associated microbiomes. However, the influence of environmental factors on mosquito populations and microbiome diversity remains underexplored. Here we examined the effects of seasonality and developed land cover on Culex mosquito abundance and bacterial diversity. Biweekly field sampling of female Culex mosquitoes was conducted using gravid and CDC light traps, spanning summer to autumn across varying developed land cover levels in two urban areas in Central Illinois. Mosquito abundance was assessed by the number of mosquitoes captured per trap night and compared across seasons and developed levels. The mean mosquito abundance for gravid and light traps was 12.96 ± 2.15 and 7.67 ± 1.44, respectively. Notably, higher levels of developed land cover exhibited higher Culex abundance than the low level for light traps, but no significant difference was found between summer and early autumn. In gravid traps, no significant differences were detected across seasons or developed levels. Microbial analysis of the mosquito microbiome revealed that Proteobacteria and Wolbachia, with a mean relative abundance of 80.77% and 52.66% respectively, were identified as the most dominant bacterial phylum and genus. Their relative abundance remained consistent across seasons and developed land cover levels, with negligible variations. Alpha diversity, as measured by observed species, Chao1, Shannon, and Simpson, showed slightly higher values in early-autumn compared to late-summer. A notable pattern of bacterial diversity, as indicated by all four diversity indexes, is evident across varying levels of land development. Significantly, high or intermediate developed levels consistently showed reduced alpha diversity when compared to the lower level. This underscores the pronounced impact of anthropogenic ecological disturbances in shaping mosquito microbiomes. Beta diversity analysis revealed no significant dissimilarities in bacterial community composition across seasons and developed levels, although some separation was noted among different levels of developed land cover. These findings highlight the significant role of environmental factors in shaping mosquito abundance and their associated microbiomes, with potential implications for the vectorial capacity in the transmission of vector-borne diseases.